Advanced charting techniques for high probability trading :the most accurate and predictive charting method ever created - Hooper, Joseph, 1943-; Zalewski, Aaron, 1980-; Watanabe, Ed. (Hoboken, N.J. : John Wiley & Sons, 2013)
"An all-star team of trading experts describe an array of proven charting techniques to bolster any portfolio. There are over 175 recognized technical indicators that have been developed by traders, mathematicians and chartists to help traders make more accurate predictions about the price movements of individual securities, asset classes and the market as a whole. These technical indicators are never used alone but applied in various combinations. Developed and tested over many years by the authors, the highly reliable strategies described in this book combine a variety of charting techniques, which, when used in conjunction, have been shown to yield extremely accurate predictions about a stock's movements through the four cyclical phases of Birth, Momentum, Exhaustion and Death"--Provided by publisher.
Introduction to advanced charting -- Straight-line chart -- Direction of a trend -- Moving average crossovers -- Bollinger Bands, PSAR, channels, zones, and FTI -- Putting it all together: MAs and the BBs -- Lower chart indicators L1 through L4 -- The second chart: Windows 2 -- Chart 2 -- Recap of advanced charting -- RS: advanced charting relative strength indicator -- Momentum trading and trading the moment.
Includes index.
Description based on print version record and CIP data provided by publisher.
Keywords: Stocks -- Charts, diagrams, etc; Investment analysis; BUSINESS & ECONOMICS -- Investments & Securities -- General; Investment analysis; Stocks; Electronic books; Charts, diagrams, etc; Electronic books